TEACHERS’ CODE-SWITCHING IN BILINGUAL CLASSROOM: EXPLORING TEACHERS’ PEDAGOGICAL FUNCTIONS AT JUNIOR SECONDARY SCHOOL - Aprilianti, Ayu; Baa, Sultan (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Among prior research on code-switching, little has been done in bilingual program particularly in junior secondary level. This research aimed to investigate the use of code-switching by bilingual teachers; their reasons use code-switching, and students’ perceptions toward teachers’ code-switching. This study used descriptive qualitative models by conducting observation, in-depth teachers’ interview and a students’ focus group discussion (FGD) as data collection. The research participants were two bilingual teachers at Junior Secondary School in Makassar, South Sulawesi, Indonesia. The obtained data were transcribed and analyzed. The study discovered that teachers employed code-switching to explain material during teaching and learning process, manage the classroom as well as establish connections with the students. Furthermore, the information gathered from the teachers’ interviews matched the observations made in the classroom. Code-switching was utilized for a number of purposes, including: 1) Efficiency; 2) Supporting Comprehension; 3) Encouraging Student Participation; 4) Clarifying Instructions; and 5) Interpersonal interactions with students. Although result of students’ FGD revealed that students had a positive attitude toward the teachers’ code-switching as it could assist them to understand the teachers explanation and instruction but they also believed code-switching could also prevent them becoming fluent in the target language